2021
DOI: 10.1042/bcj20201002
|View full text |Cite|
|
Sign up to set email alerts
|

Synergy and allostery in ligand binding by HIV-1 Nef

Abstract: The Nef protein of human and simian immunodeficiency viruses boosts viral pathogenicity through its interactions with host cell proteins. By combining the polyvalency of its large unstructured regions with the binding selectivity and strength of its folded core domain, Nef can associate with many different host cell proteins, thereby disrupting their functions. For example, the combination of a linear proline-rich motif and hydrophobic core domain surface allows Nef to bind tightly and specifically to SH3 doma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…Moreover, our current data clearly show that category IV Nef proteins containing I120 do bind and activate Hck when paired with an appropriately matched R-clamp residue at the position 83. Thus, while the findings of Choi and Smithgall on Nef from HIV-1 ELI [36] are in agreement with our data, they need to be interpreted in light of the R-clamp concept described here.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, our current data clearly show that category IV Nef proteins containing I120 do bind and activate Hck when paired with an appropriately matched R-clamp residue at the position 83. Thus, while the findings of Choi and Smithgall on Nef from HIV-1 ELI [36] are in agreement with our data, they need to be interpreted in light of the R-clamp concept described here.…”
Section: Discussionsupporting
confidence: 91%
“…This study suggested that Tyr120 would contribute to the hydrophobic pocket of Nef that accommodates the Hck SH3 domain RT-loop, whereas I120 could not serve this function. However, these molecular contacts inferred based on our (NL4-3) Nef/SH3 X-ray structure (1EFN; [9]}) would be expected to only minor rather than critical for the Nef-Hck interaction, and a recent SH3 complex structure involving HIV-1 SF2 Nef [36] does not support such a role for Y120 at all. Moreover, our current data clearly show that category IV Nef proteins containing I120 do bind and activate Hck when paired with an appropriately matched R-clamp residue at the position 83.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In HIV-1 Nef, this pocket is hydrophobic and, therefore, favours an interaction with SH3 domains that have a hydrophobic residue in the “R” position, such as Hck with an isoleucine, or the Fyn R96I and R96W mutants (referred to as I96 and W96 in this manuscript)(Arold et al, 1997; Collette et al, 2000; Horenkamp et al, 2011; Lee et al, 1996, 1995). However, the tertiary association also rearranges and fixes the SH3 RT loop onto the Nef surface, favouring SH3 domains with intrinsically more flexible RT loops (case of Hck and Fyn W96) (Aldehaiman et al, 2021; Arold et al, 1998). Thus, the stereochemical match of this SH3 residue and the Nef pocket as well as the effect of the position 96 on the RT loop flexibility control the affinity and selectivity of Nef toward SH3 domains.…”
Section: Resultsmentioning
confidence: 99%
“…HZ1 cells were transfected using TransIT-2020 reagent (Mirus) with 50 ng of Nef expression vector together with 50 ng of AP-1 pfLUC reporter plasmid [42] driving the AP-1 inducible expression of firefly luciferase, plus 50 ng of the plasmid pRL-TK (Promega) expressing low and constitutive levels of Renilla luciferase. Cells were collected and lysed with lysis buffer (Promega) on ice.…”
Section: Ap-1 Luciferase Reporter Assaymentioning
confidence: 99%